Prevalence of syphilis among people living with HIV and its implication for enhanced coinfection monitoring and management in China: A meta-analysis - Wu, Yuelin; Zhu, Wenqian; Sun, Chengqing; Yue, Xiaoli; Zheng, Min; Fu, Gengfeng; Gong, Xiangdong (Frontiers in Public Health, 2022)
Background People living with HIV (PLWH) are at an increased risk of syphilis infection. The objectives of this study were to assess the overall prevalence of syphilis among PLWH in China and identify factors associated with syphilis infection among PLWH. Methods We searched Medline, Embase, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wan-fang Data, and Chinese Biomedical Literature Database (CBM) to identify studies that reported the prevalence of syphilis among PLWH in China and were published in English or Chinese from January 1, 1990, to May 31, 2022. The reference lists of retrieved articles and relevant reviews were also checked to identify additional studies. A random-effect model was fitted to calculate the pooled syphilis prevalence among PLWH. Subgroup analyses, meta-regression analyses and sensitivity analyses were conducted to determine the potential source of heterogeneity. Results Of the 1,599 articles screened, 29 studies involving 34,740 participants were eligible for inclusion in this meta-analysis. The overall prevalence of syphilis among PLWH in China was 19.9% [95% confidence interval (CI): 15.4–24.8%, I2 = 98.9%]. Subgroup analysis showed that the pooled prevalence of syphilis among men who have sex with men (MSM) with HIV (21.9%, 95% CI: 17.2–26.9%) was much higher than that among heterosexuals (10.3%, 95% CI: 5.2–16.8%); there was regional diversity in the prevalence of syphilis, the highest in northern China (31.7%, 95% CI: 17.9–47.4%), followed by central-southern China (26.7%, 95% CI: 11.4–45.7%), and the lowest in northwestern China (15.0%, 95% CI: 6.9–25.4%); the syphilis prevalence among PLWH decreased as CD4 + T cell count increased (19.6% in CD4 + T cell < 200 vs. 8.7% in ≥ 500) and was higher among non-antiretroviral therapy (non-ART) HIV-infected patients (21.0%, 95% CI: 9.9–35.0%) than that among ART ones (16.1%, 95% CI: 3.9–34.3%). Conclusions Our study showed a significantly high prevalence of syphilis among PLWH in China, particularly among MSM with HIV. Developing national guidelines for the integrated screening, monitoring, and management of HIV and syphilis as well as syphilis diagnosis and treatment training programs for physicians at designated HIV treatment hospitals is urgent and crucial to combat HIV and syphilis coinfection in China.